2022
DOI: 10.1177/0958305x211070775
|View full text |Cite
|
Sign up to set email alerts
|

The moderating role of informal economy on financial development induced ekc hypothesis in turkey

Abstract: This study conducts an empirical investigation about the moderating role of the informal economy on Turkey's environmental performance by employing advanced econometric techniques that account numerous structural breaks in series. In this extent, we created three interaction variables by captivating the impact of informal economic activities on CO2 emissions through income, energy use, and financial sector development. Besides, we built a main effect model without the interaction variables to assess the direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Previous research has found that financial development has had an inhibitory effect on carbon emissions using a variety of methods based on data from various countries (Jalil and Feridun, 2011;Köksal et al, 2021;Tamazian et al, 2009). Financial development has been found to moderate the effect of real output on carbon emissions (in the short term, negatively), whereas financial development has been found to moderate the effect of real output on carbon emissions in the long term in Turkey (Katircioğlu and Taşpinar, 2017;Memduh Eren et al, 2022). Financial development, on the other hand, increases carbon emissions by accelerating economic growth and energy consumption, resulting in an inverted U-shaped relationship (Charfeddine and Ben Khediri, 2016;Dogan and Seker, 2016;Fan et al, 2022;Salahuddin et al, 2015).…”
Section: Financial Development and Carbon Emissionsmentioning
confidence: 99%
“…Previous research has found that financial development has had an inhibitory effect on carbon emissions using a variety of methods based on data from various countries (Jalil and Feridun, 2011;Köksal et al, 2021;Tamazian et al, 2009). Financial development has been found to moderate the effect of real output on carbon emissions (in the short term, negatively), whereas financial development has been found to moderate the effect of real output on carbon emissions in the long term in Turkey (Katircioğlu and Taşpinar, 2017;Memduh Eren et al, 2022). Financial development, on the other hand, increases carbon emissions by accelerating economic growth and energy consumption, resulting in an inverted U-shaped relationship (Charfeddine and Ben Khediri, 2016;Dogan and Seker, 2016;Fan et al, 2022;Salahuddin et al, 2015).…”
Section: Financial Development and Carbon Emissionsmentioning
confidence: 99%
“…Therefore, in the standard EKC model, the introduction of additional variables can play a crucial role in determining the shape of the relationship between development and the environment. These variables include economic openness (Dogan and Turkekul, 2016;Ozatac et al, 2017;Rana and Sharma, 2019;Koc and Bulus, 2020;Bekun et al, 2021;Pata and Caglar, 2021;Kosh et al, 2021;Pata et al, 2022;Mahmood, 2022); foreign direct investment and the quality of institutions (Biswas and Dasgupta 2012;Doytch and Uctum, 2016;Usman and Jahanger, 2021;Hussain and Dogan, 2021;Singhania and Saini, 2021;Ochoa-Moreno et al, 2021;Jahanger et al, 2022;Karim et al, 2022;Nhuong and Quang, 2022); energy consumption (Zhang et al, 2017;Ozcan and Ulucak, 2021;Jena et al, 2022); and financial development (Omri et al, 2015;Nasreen and Anwar, 2015;Memduh Eren et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…When these scarce resources are examined, there is no consensus on the EKC for the United Kingdom. While some studies (Ben Amar, 2021; Balsalobre‐Lorente et al, 2022; Caglar, Yavuz, et al, 2022; Memduh Eren et al, 2022; Farooq et al, 2022; Fong et al, 2020; Fosten et al, 2012; Jahanger, 2022; Jahanger et al, 2022; Mehmood, 2022; Neagu, 2019; Onifade & Alola, 2022; Shahbaz et al, 2017; Sephton & Mann, 2016) provide evidence for the EKC hypothesis, some studies (Ajmi et al, 2015; Ari & Şentürk, 2020; Ișik et al, 2020; Jebli et al, 2022; Kaya Kanlı & Küçükefe, 2022; Onifade, 2022) claim that the EKC hypothesis is not valid.…”
Section: Literature Reviewmentioning
confidence: 99%